UPAYA MENGHADIRKAN LARAS SALENDRO DALAM SOUNDSCAPE KEHIDUPAN SEHARI-HARI GUNA MENUNJANG MATA KULIAH SISTEM NOTASI DI PRODI KARAWITAN - Zakaria S, Mustika Iman (LP2M ISBI Bandung, 2018)
The environment is one aspect that supports the realization of a good learning process. In the process of learning Sundanese musical art, one of the materials taught in the process was the mastery of certain sounds or sounds that certainly require auditive sensitivity. scale of salendro as one of the materials that must be mastered by students becomes one of the sounds that are actually extraneous to the ears of student's soundscape. This caused the slow acceleration of the mastery of the sound. Through efforts to condition certain environments in the context of the learning process, it becomes one of the choices that must be made especially by the students themselves. Sound environment or soundscape becomes an important issue that the writer adopts, through literature studies and descriptive analysis in the context of presenting the Salendro scale tone in the daily environment of students in order to enrich the auditive experience in order to accelerate the mastery acceleration of the sound of the salendro scale.